Utilizing digital storytelling for natural textile marketing of Wastra Sejahtera Jombang - Ivena Margareta; Serli Wijaya; Oviliani Yenty Yuliana; Trixie Nova Bella Tandijaya (University of Merdeka Malang, 2025)
The Wastra Sejahtera Community Group (Pokmas) at Mojotrisno Village, Jombang Regency, is a group of natural weaving artisans facing challenges in traditional marketing, leaving many products unsold. This community service project aims to improve Pokmas’ sales performance through digital marketing with Digital Storytelling (DST) content. DST was chosen to raise brand awareness and reach wider audiences, with strategies tailored to Pokmas’ conditions, product quality, and target market. This project used a qualitative approach that included interviews with consumers who love Indonesian cloth (wastra) to understand the essential values in making consumption decisions and observed competitor strategies. We used field data to determine the DST strategy for Pokmas Wastra Sejahtera, including creating examples of DST content and training for Pokmas. We developed strategies based on consumer needs that influenced the form and content, especially in the lifestyle category and the elements that formed DST. Additionally, we simplified the DST strategy so Pokmas could adapt to structured digital marketing activities. Through this community service project, Pokmas understood and felt the benefits of exposure to a broader market when they started selling on TikTok. Through the training they find the need for DST to tell the uniqueness of wastra products.